Urinary cytology: a potential tool for differential diagnosis of acute kidney injury in patients with nephrotic syndrome - Caroline Vilas Boas de Melo (BMC Research Notes, 2020)
Abstract Objective Acute tubular necrosis (ATN) is a frequent cause of acute kidney injury (AKI). In patients with nephrotic syndrome (NS), AKI demands the differential diagnosis between ATN and rapidly progressive glomerulonephritis. In some cases, conclusive diagnosis is possible only by kidney biopsy. We aimed to study the potential use of urine cytology in the differential diagnosis between ATN and proliferative glomerular lesion in patients with NS. Results Cell size analysis showed a higher proportion of small cells and a lower proportion of large cells in the urine of patients with AKI. Cells phenotypes were easily defined using cytological preparations. Leukocytes were found to be a primary classifier of NS groups, with higher number in patients with AKI and patients with proliferative glomerular lesions. Although renal biopsy is still required for confirmative diagnosis, our data suggests that urinary cytology can be readily performed and support the differential diagnosis between proliferative glomerular lesion and ATN in patients with NS and AKI.